Antioxidant activity test of packaged juice variants of guava (psidium guajava L.) using FRAP (ferric reducing antioxidant power) method - Aprilya Sri Rachmayanti; Nahrul Hasan; Suci Fitriani Sammulia; Henny Rachdiati; Yeni Febriyanti (Science Midwifery, 2023)
Packaged juice are usually made using only one type of fruit or can be made using two types of fruits or other additional ingredients. Antioxidants are chemical compounds that can be used to protect biological components such as lipids, proteins, vitamins, and DNA. This study aims to determine the level of antioxidant activity in packaged juice drink variants of guava fruit using the FRAP (Ferric Reducing Antioxidant Power) method. The method used in this study is the FRAP method to test antioxidant activity. The results of testing the antioxidant activity with the FRAP (Ferric Reducing Antioxidant Power) method on the packaged juice drink samples, the level of antioxidant activity in juice drink sample A was 88,359 mgAAE/g sample, sample B was 88,202 mgAAE/g sample, sample C was 83,098 mgAAE/g sample, and sample D was 77,317 mgAAE/g sample. This shows that sample A demonstrated the highest antioxidant activity, followed closely by sample B, while samples C and D exhibited lower levels of antioxidant activity.